The history of invention : - Williams, Trevor I. (Facts On File, 1987)
Readers looking for information on technologies—past and present—need look no further. The History of Invention takes readers on a fascinating journey that begins with the most primitive tools and weapons and ends with the latest technological advances in communications, genetics, engineering, construction, medicine, transportation, architecture, agriculture, and space exploration...